Catalytic oxidation of cellobiose over titania-supported gold and gold-based bimetallic nanoparticles into sugar acids in aqueous medium - Prince Nana Amaniampong (2016)
Titania-supported Au and Au-M (Ru, Co, Pd, and Cu) were prepared by deposition-precipitation method using urea as a precipitating agent. The bimetallic and monometallic catalysts synthesized for this study were characterized by various techniques such as X-ray powder Diffraction (XRD), Scanning Electron Microscope (SEM), Temperature-Programmed Desorption of Ammonia (NH3-TPD), BET surface area analysis, UV-Vis spectroscopy, Transmission Electron Microscopy (TEM), X-ray Photoelectron Spectroscopy (XPS), Energy Dispersive X-ray spectroscopy (EDX) and X-ray Fluorescence (XRF). Theoretical and characterization studies of supported-Au and Au-based bimetallic catalysts have generated considerable interest. However, little research has been carried out on the catalytic activity of titania-supported Au nanoparticles and Au-M (M = Ru, Co, Pd and Cu) bimetallic nanoparticles for the oxidative conversion of cellobiose into sugar acids and polyols. In this study, it was observed that, reactions over Cu-Au/TiO2 and Ru-Au/TiO2 catalysts demonstrated excellent catalytic activities in the oxidation of cellobiose to gluconic acid, though with contrasting reaction mechanisms. For reactions over Co-Au/TiO2 and Pd-Au/TiO2 catalysts, fructose was observed as the reaction intermediate, along with small amounts of glucose. Co and Pd remarkably promoted the successive retro-aldol condensation reactions of fructose to glycolic acid, instead of the selective oxidation to gluconic acid. Furthermore, this PhD study also revealed that the reduction of titania supported Au nanoparticles catalysts at high temperature (700 oC) in hydrogen afforded excellent catalysts for oxidative conversion of cellobiose to sugar acid. Characterization results showed the gold nanoparticles pre-treated at high temperature are larger than 5 nm, which was considered as the critical diameter limit for Au nanoparticles possessing activity. Further characterization demonstrated that high temperature pretreatment changed the electronic structures of Au nanoparticles. More importantly, the high temperature pretreatment afforded a unique interface property which enhanced the electronic interaction between Au and TiO2. Also, this interface promoted the activation of oxygen and functional groups of cellobiose, resulting in the superior activity. The results in this study are well collaborated with a previous DFT calculation result. An integrated experimental and computational investigation also revealed that the surface lattice oxygen of copper oxide (CuO) activated the formyl C-H bond in glucose and incorporates itself into the glucose molecule to oxidize it to gluconic acid. The reduced CuO catalysts, initially in the form of nanoleaves, completely regained its structure, morphology and activity upon re-oxidation under mild oxygen flow. The present work utilizing CuO, for the first time, explains how lattice oxygen in the metal oxide can be used to selectively activate the aldehyde C–H bond in biomass substrates and thus, opens up new avenues to design and develop catalysts for plethora of biomass reactions that require selective activation/dissociation of the C–H bond without cleaving the C–C bond. The purpose of this study was to obtain an understanding of the nature of these catalysts and to determine if there were any relationships towards their activity for cellobiose oxidation.